Indonesian Tourism Demand by ASEAN Tourist: A Panel Data Analysis - Yulvira Rizka Putri Nugraha; Maal Naylah (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
Indonesia recorded the lowest average foreign tourist arrivals compared to ASEAN central countries, thus proving that Indonesia has yet to be thoroughly used as the primary destination for foreign tourists. Market forces influence the low number of foreign tourist arrivals in Indonesia. This study analyzes the impact of determining factors of ASEAN tourism demand in Indonesia. Panel data analysis with the Fixed Effect Model selection model was used to explore Indonesia’s tourism demand from five ASEAN countries from 2001 to 2020. The results showed that tourist expenditure, CPI, terrorism, and COVID-19 significantly negatively affect the number of Indonesian tourist visits. In contrast, the exchange rate and GDP per capita significantly positively impact the number of Indonesian tourist visits. Indonesia needs to improve the quality of tourism products and services to increase foreign tourist arrivals and implement international cooperation to create promotions for domestic tourism.JEL Classification: C33, L83, Z3How to Cite:Nugraha, Y. R. P., & Naylah, M. (2022). Indonesian Tourism Demand by ASEAN Tourist: A Panel Data Analysis. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 45-56. https://doi.org/10.15408/sjie.v12i1.27999.